Remote sensing techniques for interpretation of landsurface physical variables related to hydrological phenomena in Lembang Area, West Java, Indonesia - Totok Gunawan (Indonesian Journal of Geography, 1988)
The variables related to the hydrological processes within a watershed are considered in four categories: climate, landsurface physical processes, and output variables. Based on the properties of the image of the remotely sensed document, landsurface physical variable is one of these categories which is directly visible on the image, in a broad sense, they may vary from landform to geometrical aspect of channel. On the other hand, features that are not visible on the image, such as, underlying formation, can be deduced from related features that are directly visible.The principal methods of aerial photographic interpretation based on the pattern analysis of the landscape features and the division to the smaller features, are characterized by local pattern elements. The aims of the study are: (i) to get appropriate information about landsurface physical variables through aerial photographic interpretation, (ii) to determine and describe the interrelationship between selected landsurface physical variables and the hydrological processes.The geologic structure of•fault of Lembang area changes the landsurface physical condition, such as, surface drainage pattern, drainage density, landform and local slope, and land use. This fault and the landsurface physical changes appear on the image clearly. The development of the surface drainage is shown quite differently between